Pengembangan Budaya Organisasi Dalam Mewujudkan Lembaga Pendidikan Islam Unggulan: (Studi Deskriptif Kualitatif di SDIT Darul Falah Sukorejo Ponorogo) - Roni Harsoyo; Sulistyorini; Samsudin (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2020)
The context of this research is the biggest challenge of schools/’madrasah’ in carrying out the mandate related to the quality of education which is a measure of the success of the implementation of education, one of which is to shape the character/personality of students through inheritance of cultural values. In educational institutions, organizational culture (values, habits, and positive attitudes) will be a strong non-material capital strength for the realization of excellent educational institutions. This study aims to describe the organizational culture developed by SDIT Darul Falah Sukorejo Ponorogo which makes it one of the leading schools in Ponorogo Regency. This type of research is descriptive qualitative research based on field research. The results showed that the organizational culture developed by SDIT Darul Falah included: 1) at the institutional level which included weekly meetings, field meetings, routine recitals every Ahad Wage, One Day One Information (ODOI), educational visits and flag ceremonies every Monday; 2) at the level of educators and educational staff which includes bina nafsiyah, tahsin al-Qur'an, professional development; and 3) at the student level which includes bina nafsiyah, reading the Koran with the Ummi Method, congregational prayers, manners, queuing, independent, disciplined, One Day One Thousand (ODOT), skilled, healthy living, clean and beautiful.